Vida Alone and in Tank Mixtures for Spring Kochia Control in Fallow - R. S. Currie; P. W. Geier; G. W. Boyer; P. W. Stahlman (Kansas Agricultural Experiment Station Research Reports, 2018)
No herbicide treatment provided more than 50% kochia control at Garden City, KS, or 80% kochia control at Hays after the first week of application. At Garden City, KS, treatments of Vida (pyraflufen) plus glyphosate and 2,4-D or dicamba, glyphosate alone, or glyphosate plus 2,4-D or dicamba provided greater than 89% kochia control. At Hays, glyphosate alone or with 2,4-D, and Vida plus dicamba alone or with glyphosate had greater than 85% control of kochia.
Keywords: Early postemergence